LANSKAP LINGUISTIK KOTA MEDAN: KAJIAN ONOMASTIKA, SEMIOTIKA, DAN SPASIAL - Sahril Sahril; Syahifuddin Zuhri Harahap; Agus Bambang Hermanto (Balai Bahasa Sumatera Utara, 2019)
Language is a marker of social change that occurs in society. Prescriptivism, which is more glorifying language that is considered more modern. Linguistic landscape views urban as text. The meaning is, because language is widely used in public spaces in urban areas. Linguistic landscape is the presence of language between space and place. An interdisciplinary study of the presence of various language issues that interact with other languages in the public sphere. This study describes the phenomenon of linguistic landscape in Medan in the categories of onomastics, semiotics and spatial. The method used, namely qualitative research methods. The research threat uses the linguistic landscape theory of the Landry & Bourhis (1997) model. The research findings are the use of foreign languages that dominate the landscape in Medan City. Indonesian is no longer the sole authority in a region. Found onomastical, semiotic, and spatial aspects in the linguistic landscape in the city of Medan.